GAMBITS FOUND IN THE CONVERSATIONS OF LOOK AHEAD 2 (An English Textbook for Senior High School Students Year XI Published by Erlangga) (ELT Forum: Journal of English Language Teaching, 2013)
This is a descriptive qualitative study aiming at finding out what speech acts and gambits found in the conversation models of Look Ahead 2 (an English textbook for senior high school grade XI published by Erlangga). This study was conducted in line with the important roles of gambits in spoken communication.Searle (1969) classified speech acts into five: directives, commissives, representatives, declaratives and expressive with further sub-classified by van Ek (1998) into six functions and 132 sub-functions. These speech act functions have become the basis of English curriculum in Indonesia. The speech acts realizations in utterances are usually hedged by gambits or discourse markers aiming at downgrading, upgrading, intensifying or avoiding a Face Threatening Act. The data were collected from the textbook Look Ahead 2 written by Th. M. Sudarwati and Eudia Grace. The study was focused only on five speech acts: asking for an opinion, giving opinion, agreeing to an opinion, disagreeing to an opinion, and giving suggestion/advice. Therefore, the data taken were only the sentences which indicate those five speech acts.16 conversations were taken as the data.  There were 38 clauses belonging to 11 speech act functions specified for XI grade students. The speech acts found were: asking for an opinion, giving opinion, expressing satisfaction, dissatisfaction, giving suggestion, warning, expressing relief, pain, sorrow, anger, and annoyance. There were 34 gambits found in five speech acts: four gambits were found in asking for an opinion, six in giving opinion, five in agreeing to an opinion, ten in disagreeing to an opinion, nine in giving suggestion/advice. Of the five speech acts understudy, there were three types of gambits namely opening, linking, and responding gambits. There were nine gambits belong to opening gambit, three gambits belong to linking gambit, and 22 data for responding gambit.The finding indicated that among 14 speech acts required by the curriculum, 11 speech acts were found but the other three were not. They are expressing pleasure, expressing love and expressing embarrassment. The gambits found in five specific speech acts were used appropriately based on both Keller’s and Dörnyei’s classifications. Among three types of gambits, opening gambit was the most frequently used (52.9%). Responding gambit was the second frequently used (38.2%), and the least frequently used gambit was the linking gambit (8.8%).